(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Abstract Rape has long been a contentious issue in our culture, but it wasn’t a focus of mainstream research until the 1970s, when the feminist movement gained momentum, and society’s awareness of the gender gap increased. Rape then became a hot topic in criminological, sociological, and psychological literature. The general public anticipates fairness from the police and expects them to be unbiased. Victims anticipate that the police will treat their complaints fairly when they come to them for assistance. It should be mandated that police provide survivors with reports. The most significant indicator of training is whether or not a police investigator follows SOPs, which are the rules, procedures, and benchmarks required for a company to flourish. The best ability of a police investigator to solve rape cases is to be honest when resolving crimes and to not be partial while gathering evidence. While the capacity of a police investigator to solve problems with curiosity appears to be the least significant talent of an investigator in solving rape cases. A lack of technical proof, such as CCTV cameras, a lack of evidence to support an inquiry, lying or making blatantly false statements on a major topic, and the absence of a witness. Furthermore, conducting seminars for awareness of rape cases in the vicinity of police stations and creating ads to educate the community.